Preventive Treatment on Sexual Abuse Survivor with Mental Retardation - Shinta Brisma; Nurmiati Amir (HM Publisher, 2020)
The existence of limitations for children with mental retardation causes aninability to protect themselves so that they often become victims of sexualharassment. Preventive efforts are something that needs to be improved forprevention, considering the worse risks to children. The importance of an effortto prevent sexual abuse of children with mental retardation in connection withthe lack of knowledge about sexual abuse and the inability of children to facethe dangers that threaten themselves. From the results of research conductedin the United States in 1994, nearly 90% of children with mental retardationdisorders had experienced sexual abuse, as many as 49% had experiencedsexual abuse more than ten times. The high incidence of sexual abuseexperienced by children with mental retardation is due to various factors,namely the condition of children's limitations, lack of supervision andprotection of children by parents and the environment. Efforts that can be madeare increasing knowledge about sexual abuse and self-protection skills throughthe Behavioral Skills Training Group Program, where children are trained torecognize threatening objects and situations (sexual abuse). Increasingknowledge about sexual abuse and providing training (self-protection skills) isa significant primary preventive measure to reduce the risk of sexual abuse inchildren with mental retardation.